Development of student worksheet based on MIKiR approach for fifth students’ learning science - Mayasari L. Tobing; Neni Hermita; Gustimal Witri (Indonesian Journal of Science, Technology, Engineering, Art, and Mathematics Education, 2022)
This research is motivated by the importance of developing student worksheets (LKPD in Indonesia term) in order to make students active in learning. LKPD aims to facilitate educators in carrying out learning. This study uses research and development (R&D) method, according to the ADDIE model development procedure (analyze, design, development, implementation, and evaluation). Data collection techniques in this study were using interview sheets, and questionnaires to test products by validators (educational technology experts, material experts and linguists), teacher response tests, and student response tests. The study produces LKPD based on MIKiR approach on the topic of heat and its transfer, MIKiR is an a learning approach consists of mengalamai (experiencing), interaksi (interaction), komunikasi (communication), and refleksi (reflection) activities which are part of active learning activities. The results of the validation data analysis show that the LKPD meets the very valid criteria. Teachers and students also gave a high score to the feasibility of the LKPD based on MIKiR approach. Therefore, MIKiR-based LKPD on heat and transfer materials are very suitable to be used as one of the active teaching materials in supporting fifth grade students’ learning science.